Seasonal variation of immune response to heterologous erythrocytes in natural populations of red-backed (Clethrionomys rutilus) and gray-sided (C. rufocanus) voles in Western Siberia - Kravchenko, Larisa B. (Ecology and evolution)
We studied the seasonal variation of adaptive humoral immunity (AHI) in northern red-backed vole (Clethrionomys rutilus Pallas, 1779, RBV) and gray-sided vole (C. rufocanus Sundevall, 1846, GSV) in Tomsk region of Western Siberia. Immunoresponsiveness (IR) to sheep red blood cells was assessed by the number of antibody-producing cells in the spleen. The use of a generalized linear model to analyze the effects of species, sex, year of research, and season of withdrawal of individuals from nature on IR showed a significant effect of species identity, season of animal capture, and the interaction of species with season. The RBV demonstrated higher immune responses during a year, and both species had higher IR in winter. Suppression of IR in spring was greater, started earlier, and lasted longer (March-May) in GSV. In RBV, immunosuppression was restricted to April. The significant negative within year correlations of IR with body mass and masses of reproductive organs in GSV indicated a trade-off between AHI and growth and reproduction processes. A probable explanation for the difference between species in the seasonal variation of AHI may be related to the difference in tropho-energetic requirements of each vole species. GSV is a predominantly herbivorous rodent and its thermoregulation seems less efficient than of RBV. The deeper spring immunosuppression in GSV may explain in part its higher mortality during the season of colds.